The Influence of Organizational Culture on Business Process Management: An Update of a Systematic Literature Review - Lima, Willinny Karla; Barbosa, Anderson F.; Silva, Andyson; Santos, Jonathan; Pinto, Hywre; Almeida, Glenda; Vilela, Jéssyka (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Organizational culture is a factor that influences Business Process Management (BPM) initiatives, impacting the effective implementation and adoption of continuous improvement, innovation, and strategic alignment practices, both in the organizational dimension and in human interactions between team members. Problem: The implementation of BPM is hampered by cultural barriers, such as resistance to change and risk aversion. These issues negatively affect operational efficiency and employee satisfaction. Solution: The proposed solution consists of identifying and analyzing the cultural aspects that influence the adoption of BPM. IS Theory: The study is based on the Innovation Adoption Theory, which explores how and why innovations are adopted in various organizational contexts. Method: The method adopted consisted of an update of the systematic literature review, with data from 2011 to 2024. A mapping of the previous study supported this study. Summary of results: The results indicate that companies with a culture focused on innovation and collaboration have a significantly higher BPM adoption rate, highlighting the importance of an adaptive cultural approach. Contributions and Impact on the IS area: The contributions include the identification of cultural practices that facilitate the adoption of BPM, and providing practical guidelines for academics and professionals. The impact on the area of Information Systems (IS) is that it highlights the potential of organizational environments that are conducive to innovation, improving the effectiveness and efficiency of IS.